A two-component active targeting theranostic agent based on graphene quantum dots1. Issue 17 (7th May 2015) - Wang, Xiaojuan; Sun, Xing; He, Hua; Yang, Hao; Lao, Jun; Song, Yanzhuo; Xia, Yongqing; Xu, Hai; Zhang, Xiaodong; Huang, Fang
<x xml:space="preserve">Abstract</x> Selective tumour cell imaging and synergistic anti-cancer therapeutics are achieved by using the conjugate of AS1411 and graphene quantum dots.